Pgrmc1 Knockout Impairs Oocyte Maturation in Zebrafish - Wu, Xin-Jun; Thomas, Peter; Zhu, Yong (Frontiers in Endocrinology, 2018)
Recent investigations suggest progestin receptor membrane component 1 (PGRMC1) associates with and transports a wide range of molecules such as heme, cytochromes P450, steroids with 21 carbons, membrane progestin receptor alpha (mPRα/Paqr7), epidermal growth factor receptor (EGFR), and insulin receptor. It is difficult to discriminate the true functions of PGRMC1 from the functions of its associated molecules using biochemical and pharmacological approaches. To determine the physiological function(s) of PGRMC1, we generated global knockouts for pgrmc1 (pgrmc1−/−) in zebrafish. We found a reduction in both spawning frequency and the number of embryos produced by female mutants. We also observed reduced sensitivity of fully-grown immature oocytes to a progestin hormone and a reduced number of oocytes undergone meiotic maturation both in vivo and in vitro in pgrmc1−/−. This reduced sensitivity to progestin corresponds well with significant reduced expression of mPRα, the receptor mainly responsible for mediating oocyte maturation and meiosis resumption in fish. The results provide in vivo and in vitro evidence for the physiological functions of Pgrmc1 in oocyte maturation and fertility, as well as a plausible molecular mechanism via regulation of mPRα, which in turn directly regulates oocyte maturation and affects fertility in zebrafish.